Laser Stripe Extraction for 3D Reconstruction of Complex Internal Surfaces - Xiaowei Zhao; Daguo Yu; Hongyan Shi (IEEE Access)
Extracting the laser stripe center is crucial for 3D reconstruction using laser triangulation. However, automatically extracting laser stripes from complex surfaces is a challenging task. In this work, we have improved upon the Steger method and introduced a new laser stripe identification technique called the Breakdown Discharging Method. This method transforms the laser stripe extraction process into an electrical breakdown problem, where the path of discharge across an insulating medium’s surface is tracked to extract the laser stripe centerline. The primary advantage of the Breakdown Discharging Method lies in its ability to optimize the extraction of laser stripe centerlines, even on complex surfaces where the stripe may be unevenly illuminated or discontinuous—tasks that existing methods struggle to accomplish. Results from various complex surfaces demonstrate that the Breakdown Discharging Method is highly robust, effectively adapting to laser stripes on intricate shapes. This novel extraction method will advance the application and development of 3D reconstruction for objects with complex shapes.